PENDEKATAN ANALISIS TRANSAKSIONAL DALAM KONSELING - Wahid, Lalu Abdurrachman (Jurusan Bimbingan dan Konseling Islam Fakultas Dakwah dan Komunikasi IAIN Mataram, 2016)
Transactional analysis examines the transaction is done by some individuals who have their own special personality. The transaction is an activity between two or more persons that gives influence on each other. Transactional analysis is rooted in the foundation of anti-deterministic philosophy emphasized that human being is able to go beyond conditioning and initial programming. Transactional analysis is transactional psychotherapy can be used in individual therapy, however it is better used in group therapy. The word of transaction always refers to the rocess of exchange in a relationship. In interpersonal communication is also known as transaction exchanged messages, either verbal or non-verbal. Transactional analysis is a type of communication analysis where every single person placed himself/herself according to the position of the different psychology. The purpose of transactional analysis was to assist individuals in order to have freedom to choose, freedom to change desire, freedom to change some responses toward common or new stimulus.